Dr. Juan Carlos Monroy — Deep Plane Facelift — Bogotá - Monroy, Juan Carlos (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Juan Carlos Monroy, practicing in Bogotá, Colombia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003339; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; colombia; bogotá